2014
DOI: 10.4049/jimmunol.1400700
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Remodeling of Tight Junctions during Paracellular Diapedesis in a Human Model of the Blood–Brain Barrier

Abstract: Leukocyte transendothelial migration (TEM; diapedesis) is a critical event in immune surveillance and inflammation. Most TEM occurs at endothelial cell borders (paracellular). However, there is indirect evidence to suggest that at the tight junctions of the blood-brain barrier (BBB), leukocytes migrate directly through the endothelial cell body (transcellular). Why leukocytes migrate through the endothelial cell body rather than the cell borders is unknown. To test the hypothesis that the tightness of endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 66 publications
3
81
0
2
Order By: Relevance
“…Winger and colleagues have observed that human monocytes were able to cross the endothelial tight junction by transiently breaking the local claudin-5 architecture. 72 Non-junctional claudin-5 molcules were rapidly mobilized to form foci surrounding the tight junction gap, which ensured the re-sealing of tight junction after leukocyte extravasation.…”
Section: The Structural Basis Of Bbb Tight Junction Permeabilitymentioning
confidence: 99%
“…Winger and colleagues have observed that human monocytes were able to cross the endothelial tight junction by transiently breaking the local claudin-5 architecture. 72 Non-junctional claudin-5 molcules were rapidly mobilized to form foci surrounding the tight junction gap, which ensured the re-sealing of tight junction after leukocyte extravasation.…”
Section: The Structural Basis Of Bbb Tight Junction Permeabilitymentioning
confidence: 99%
“…TJ disruption precedes overt lesion formation and correlates with clinical severity of EAE (Alvarez et al, 2015; Fabis et al, 2008). Moreover, endothelial TJ degradation promotes paracellular leukocyte migration (Reijerkerk et al, 2008; Winger et al, 2014), whereas overexpression of Claudin1 is protective for EAE (Pfeiffer et al, 2011). Endothelial TJs also prevent serum proteins such as fibrinogen from crossing the BBB, thereby conferring disease protection (Ryu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Âìåñòå ñ òåì èìåííî â ó÷àñòêàõ âîñïàëåíèÿ èíè-öèèðóþòñÿ ïðîöåññû ðåïàðàòèâíîãî íåéðîãåíåçà è àí-ãèîãåíåçà.  öåëîì, ñòðóêòóðíàÿ öåëîñòíîñòü ÃÝÁ íà-ðóøàåòñÿ èç-çà ñíèaeåíèÿ ýêñïðåññèè èëè íàðóøåíèÿ ñáîðêè áåëêîâ òåñíûõ êîíòàêòîâ, ïîâðåaeäåíèÿ áàçàëü-íîé ìåìáðàíû ÃÝÁ, ãèáåëè ýíäîòåëèîöèòîâ, ÷åìó äî-ïîëíèòåëüíî ñïîñîáñòâóþò èçìåíåíèÿ âçàèìîäåéñò-âèé ìåaeäó êëåòêàìè ýíäîòåëèÿ è ïðèëåaeàùèìè àñòðî-öèòàìè [23,60,78]. Êàê ñëåäñòâèå, â ïåðèôåðè÷åñêîé êðîâè îïðåäåëÿþòñÿ "çàáàðüåðíûå" áåëêè, áåëêè-ìàð-êåðû ïîâðåaeäåíèÿ ÃÝÁ (ôàêòîð ðîñòà ýíäîòåëèÿ ñîñó-äîâ (VEGF), íåéðîòðîôè÷åñêèé ôàêòîð ìîçãà, ãëèàëü-íûé ôèáðèëëÿðíûé êèñëûé áåëîê, íåéðîíñïåöèôè÷å-ñêàÿ åíîëàçà, ìîëåêóëà ãëàâíîãî êîìïëåêñà ãèñòîñîâ-ìåñòèìîñòè II êëàññà, ìîëåêóëà êëåòî÷íîé àäãåçèè àêòèâèðîâàííûõ ëåéêîöèòîâ, ñåìåéñòâî ïðîòåèíîâ S100, êëàóäèíû, îêêëþäèíû, êàäãåðèíû, ñåêðåòèðóå-ìûå àñòðîöèòàìè áåëêè Shh, Wnts, Norrin), à òàêaeå ìå-òàáîëèòû (íàïðèìåð, ãëóòàìàò) è öèòîêèíû, ñâèäå-òåëüñòâóþùèå î ôåíîìåíå "ïðîðûâà" ÃÝÁ) [3,12,40,69].…”
Section: íàðóøåíèÿ ñòðóêòóðíîé è ôóíêöèîíàëüíîé öåëîñòíîñòè ãåìàòîýíöunclassified